2016
DOI: 10.1136/bjsports-2016-096343
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced biochemical changes and their potential influence on cancer: a scientific review

Abstract: AimTo review and discuss the available international literature regarding the indirect and direct biochemical mechanisms that occur after exercise, which could positively, or negatively, influence oncogenic pathways.MethodsThe PubMed, MEDLINE, Embase and Cochrane libraries were searched for papers up to July 2016 addressing biochemical changes after exercise with a particular reference to cancer. The three authors independently assessed their appropriateness for inclusion in this review based on their scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 168 publications
2
93
0
2
Order By: Relevance
“…Another possible mechanism is that PA decreases the amount of visceral fat. Oestrogen and the neuropeptide cytokine leptin are generated in fat cells, especially in post‐menopausal women (Thomas, Kenfield, & Jimenez, ). This may be one explanation for the larger effect of PA in older women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible mechanism is that PA decreases the amount of visceral fat. Oestrogen and the neuropeptide cytokine leptin are generated in fat cells, especially in post‐menopausal women (Thomas, Kenfield, & Jimenez, ). This may be one explanation for the larger effect of PA in older women.…”
Section: Discussionmentioning
confidence: 99%
“…Age at diagnosis, years, mean (SD) 59.6 (9.8) are generated in fat cells, especially in post-menopausal women (Thomas, Kenfield, & Jimenez, 2017). This may be one explanation for the larger effect of PA in older women.…”
Section: Characteristics Mean (Sd)/n (%)mentioning
confidence: 99%
“…Furthermore, both indirect and direct effects of exercise may be therapeutic in this population, as demonstrated by Robert Thomas’ group 5. We see this concept of individualisation make a reappearance in the review article regarding exercise and brain health by Canada Research Chair, Dr Teresa Liu-Ambrose 6…”
Section: Pushing the Envelope In Exercise Medicine Toomentioning
confidence: 89%
“…Regular exercise has been shown to decrease the incidence of mortality in cancer and it is suggested that this could be partly due to the fact, that exercise increases the activity of DNA repair enzymes [110]. Oxidative DNA base damage is primarily repaired via the base excision repair pathway that is initiated by DNA glycosylases.…”
Section: Base Excision Repairmentioning
confidence: 99%